New Challenges for Higher Education and the Future of Higher Education Research - Teichler, Ulrich (South African Journal of Higher Education, 2016)
Reflections on the future of higher education have occasional¬ly been undertaken by supra-national organisa¬tions as well as by higher education researchers. They are considered necessary because higher education has an impact on future scholars and future professionals for several decades to come. Also, research has addressed potentially relevant issues of higher education often before the decision makers themselves, through increased public awareness of respective problems, are obliged to deliver results. Even though many future scenarios are shaped too much by issues of the recent past, a review of major current issues in higher education is the customary starting point for scenario planning. It might be important in the near future that higher education aims to be socially relevant without becoming overly instrumental. Moreover, a scope of diversity has to be found that serves the existing multiplicity of people and functions without ending up in over-competitiveness for positions in a steeply stratified higher education system. Finally, a vision is needed how higher education could serve a ‘highly educated society’ or a ’mass knowledge society’ in which the majority of the population is highly informed, highly reflective and able to share responsibilities.